Instant beef stew / Nursyadah Nordin, Norhidayah Abdullah and Muna Shakirah Mohamad - Nordin, Nursyadah; Abdullah, Norhidayah; Mohamad, Muna Shakirah (2021)
The food industry is familiar with an instant cream-based soup such as chicken soup, mushroom soup, and tomato soup. For this type of food range, it is commonly consumed by those who desire fast and simple meal that can fulfill their hunger immediately. This product represents simplicity and instantaneous as it can fulfill consumer's desire to consume savory food in less than 5 minutes. Cream based soup is basic; therefore, this instant beef stew is the new highlight to the range. It is rich with flavor and nutrients as the stew was made with vegetables and beef that high in vitamins, carbohydrates, and protein that can make the consumer felt satisfied just by consuming a clean meal. This instant beef stew can be used as a base for various meals for example as a mash potato gravy and seasoning to your stir-fried vegetable. Because it is produced in the form of powder, it can last at room temperature for more than three months. For those who love traveling and adventure, the instant beef stew is suitable for this type of consumer as it is practical, easy to make, and consumes less space in the backpack. To conclude, this new product is simple, convenient and travel friendly. It is suitable to be consumed by everyone regardless of age, race, and gender.